A next generation of conditional cash transfer programs - Neri, Marcelo (2017)
This article evaluates the role played by Brazilian federal conditional cash transfer programs (CCTs) such as Bolsa Família and Bolsa Escola during the recent years and discusses their future. Previous empirical evidence is organized, proposing an integrated framework with two complementary perspectives. The first perspective is a goal approach based on the short term aggregated influences exerted by these programs organized under four headings, namely: equality, prosperity, stability and sensibility. The emphasis here will be to compare the results of Bolsa Família with other official programs such as BPC and Social Security benefits. The second perspective follows a means approach inspecting the microeconomic mechanisms through which CCTs operate comparing the impacts on CCTs beneficiaries versus non-beneficiaries. It is useful to consult the details of previous works on CCTs and to discuss possible desirable upgrades.